Portfolio Adjustment and Monetary Growth - Johnson, Lewis (Review of Economic Studies, 1976)
Journal Article Portfolio Adjustment and Monetary Growth Get access Lewis Johnson Lewis Johnson Federal Reserve System Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 3, October 1976, Pages 475–481, https://doi.org/10.2307/2297226 Published: 01 October 1976 Article history Received: 01 February 1974 Accepted: 01 November 1975 Published: 01 October 1976